2022
DOI: 10.1016/j.biopha.2021.112377
|View full text |Cite
|
Sign up to set email alerts
|

CYP450 drug inducibility in NAFLD via an in vitro hepatic model: Understanding drug-drug interactions in the fatty liver

Abstract: Drug-drug-interactions (DDIs) occur when a drug alters the metabolic rate, efficacy, and toxicity of concurrently used drugs. While almost 1 in 4 adults now use at least 3 concurrent prescription drugs in the United States, the Non-alcoholic fatty liver disease (NAFLD) prevalence has also risen over 25%. The effect of NALFD on DDIs is largely unknown. NAFLD is characterized by lipid vesicle accumulation in the liver, which can progress to severe steatohepatitis (NASH), fibrosis, cirrhosis, and hepatic carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Additionally, information on alterations to biotransformation enzymes can provide insight into the possibility of PFAS exposure causing disruptions to endogenous functions and drug metabolism by CYP450 enzymes. CYP enzymes play a crucial role in the metabolism of xenobiotics, and changes in their activity or expression can affect the toxicity and efficacy of pharmaceuticals ( Rey-Bedon et al 2022 ). Disruptions to biotransformation pathways can also lead to dysfunctions in intracellular processes created by an inability to regulate fatty acid metabolism and the accumulation of unmetabolized harmful substrates ( Deodhar et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, information on alterations to biotransformation enzymes can provide insight into the possibility of PFAS exposure causing disruptions to endogenous functions and drug metabolism by CYP450 enzymes. CYP enzymes play a crucial role in the metabolism of xenobiotics, and changes in their activity or expression can affect the toxicity and efficacy of pharmaceuticals ( Rey-Bedon et al 2022 ). Disruptions to biotransformation pathways can also lead to dysfunctions in intracellular processes created by an inability to regulate fatty acid metabolism and the accumulation of unmetabolized harmful substrates ( Deodhar et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, authors in various pieces of research have concluded that liver fat excess could cause severe drug–drug interactions in patients with obesity-related NAFLD or nonalcoholic steatohepatitis. These interactions are related to the CYP2B6 and CYP2C9 enzymes [ 154 , 155 , 156 ]. The generation of ROS inside and outside of hepatocytes, the formation of reactive metabolites at hepatic level, the modification of covalent bonds between constituents of cells with drugs and their metabolites, the activation of signal transduction pathways that alter necrosis or apoptosis or survival pathways, characterised by wide-ranging changes in gene expression (i.e., impacting on the regulation of transcriptional and post-transcriptional activities) coupled with mitochondrial damage, which ends up in altering ATP generation, are all principal mechanisms of drug-induced hepatotoxicity [ 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, experimental and clinical studies report consistently that CYP3A4 is downregulated in fatty liver in terms of either activity, expression level, or pharmacokinetics (PK) 9 13 . In contrast, most but not all human and animal studies state that CYP2E1 is upregulated in non-alcoholic steatohepatitis in terms of either activity or expression 9 , 10 , 14 16 . In contrast, it was also observed in patients that CYP2E1 is downregulated in terms of protein and mRNA expression 17 .…”
Section: Introductionmentioning
confidence: 95%